Financial distress BUMN di Indonesia: Studi pada perusahaan go-public tahun 2017-2022 - Susatyo Bahrum; Susanto S. Hariranto; Sekar Mayangsari (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
The aim of this research is to analyze whether there is an influence of the variables profitability, leverage, company size, volatility, and audit quality on the financial distress of Go-Public Companies in 2017-2022. This research contributes to covering the gap in differences in previous research results while providing a different perspective by using corporate sector moderating variables in analyzing the financial distress of Go-Public BUMN in Indonesia. The data population that will be used is Go-Public companies listed on the Indonesia Stock Exchange (BEI) in the research period 2017-2022. The research results show that partially leverage has a negative effect and company size has a positive effect on financial distress, while stock volatility has no negative effect and audit quality has no positive effect on financial distress of BUMN in Indonesia as proxied by the Altman Z-Score value. However, simultaneously, these four variables have an influence in predicting the financial distress of BUMN listed on the Indonesia Stock Exchange for the 2017-2022 period. The moderating variable in this study shows that all sectors examined in this study are able to provide a negative moderating impact on audit quality and a positive impact on the company size variable.